Pengaruh Kemandirian Belajar Terhadap Kemampuan Penalaran Matematis Siswa Kelas VIII SMP Negeri 1 Loea - Marniati; Jahring; Wayan Yuliani (Arden Jaya Publisher, 2021)
The formulation of the problem in this study are: (1) How is the description of the learning independence of class VIII students of SMP Negeri 1 Loea?; (2) What is the description of the mathematical reasoning ability of eighth grade students of SMP Negeri 1 Loea?; (3) Is there a significant effect between learning independence on the mathematical reasoning ability of eighth grade students of SMP Negeri 1 Loea?. This research is a quantitative research with the type of Ex Post Facto research. The population in this study were all grade VIII students of SMP Negeri 1 Loea for the academic year 2020/2021 with a sampling technique that was simple random sampling where sample members from the population were taken randomly without regard to the strata in the population. So that the sample in this study amounted to 30 people. The data collection technique in this study was a learning independence questionnaire and a matter of mathematical reasoning ability. Data analysis used simple regression analysis. The results of the regression equation obtained in this study are The results of this study indicate that: (1) Descriptively from the data on the learning independence of class VIII SMP Negeri 1 Loea students are in the high category, based on the average student learning independence of 65, 51 so that it can be concluded that the learning independence of class VIII SMP Negeri 1 Loea students is in the high category; (2) Descriptively from the data on the mathematical reasoning ability of class VIII SMP Negeri 1 Loea is in the less category based on the average mathematical reasoning ability of students which is 40.33 so it can be concluded that the mathematical reasoning ability of class VIII students of SMP Negeri 1 Loea is at less category.; (3) There is a significant effect between learning independence on the mathematical reasoning ability of class VIII students of SMP Negeri 1 Loea, this can be seen from the results of the F test calculations, where the results of the F test calculations get Fcount = 12.257 while the Ftable value is 4, 20. because Fcount = 12,257 > Ftable = 4,20, it can be concluded that there is a significant influence between independent learning on the mathematical reasoning ability of eighth grade students of SMP Negeri 1 Loea; (4) From the analysis of the coefficient of determination obtained a score of 0.307, which means that students' mathematical reasoning ability is influenced by independent learning with 31% and the remaining 69% is influenced by other factors.